1996
DOI: 10.1016/0001-4575(96)00004-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retroreflector positioning on nighttime recognition of pedestrians

Abstract: This field study investigated potential effects of retroreflector positioning on recognition of nighttime pedestrians. The subject's task was to press a response button whenever he/she recognized a pedestrian on or alongside the road, while in a car with low-beam lamps on that was driven at a constant speed on a dark road. The results showed that each retroreflector configuration yielded significantly longer recognition distances than the no-retroreflector configuration. More importantly, the retroreflective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…Researchers have also begun to identify the neural mechanisms involved in the perception of biomotion (Grossman et al, 2000(Grossman et al, , 2005. Meanwhile, there has been interest in capitalizing on our perceptual sensitivity to biomotion in order to enhance drivers' ability to recognize pedestrians (including road workers), from a safe distance at night (Balk et al, 2008;Blomberg et al, 1986;Luoma and Penttinen, 1998;Luoma et al, 1996;Owens et al, 1994;Sayer and Mefford, 2004;Tyrrell et al, 2009;Wood et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also begun to identify the neural mechanisms involved in the perception of biomotion (Grossman et al, 2000(Grossman et al, , 2005. Meanwhile, there has been interest in capitalizing on our perceptual sensitivity to biomotion in order to enhance drivers' ability to recognize pedestrians (including road workers), from a safe distance at night (Balk et al, 2008;Blomberg et al, 1986;Luoma and Penttinen, 1998;Luoma et al, 1996;Owens et al, 1994;Sayer and Mefford, 2004;Tyrrell et al, 2009;Wood et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research by our group and others has demonstrated that pedestrians are even more conspicuous to drivers at night when retroreflective material is attached to the pedestrian's major moveable joints (Balk et al, 2008;Blomberg et al, 1986;Luoma and Penttinen, 1998;Luoma et al, 1996;Owens et al, 1994;Sayer and Mefford, 2004;Tyrrell et al, 2009;Wood et al, 2005). Using a variety of methods (laboratory-based videos and closed and open-road evaluations), these studies have demonstrated that retroreflective strips positioned in the full biomotion pattern provide substantial advantages for improving pedestrian visibility, which result more from the pedestrian's motion than from highlighting the pedestrian's form (Balk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Attempting to equate the amount of retroreflective areas between conditions, Luoma et al (1996) report a field study in which participants performed a recognition task while being driven in a car travelling at 50 km/h. In this experiment, pedestrians appeared either crossing the road or walking towards the experimenter and were filmed in a single, unilluminated road environment.…”
mentioning
confidence: 99%
“…Studies also show that the positioning and color of retro-reflective material is important. One study reported that retro-reflective markings attached to arms or legs produced recognition distances 60 to 80% greater than markings attached to the torso, which in turn had twice the recognition distance than pedestrians without any markings at all (Luoma, Schumann, & Traube, 1996). Examining the visibility of retro-reflective material, one study demonstrated that materials reflecting red, yellow, and green colors were detected at similar distances at night, and all at significantly greater distances than white materials of the same intensity (Sayer, Mefford, Flannagan, Sivak, Traube, & Kojima, 1998).…”
Section: Pedestrian Conspicuity and Visibilitymentioning
confidence: 99%